Age-specific anthropometric characteristics variation rates in speed skating sport - Bakanov, M. V.; Voronin, D. M.; Titlov, A. V. (Theory and Practice of Physical Culture, 2019)
Multiple study reports and analyses show that the athletes` adaptation to physical trainings is age-specific, with the adaptation responses in every age group depending on the training models and intensities. Thus the adolescent cardiovascular system growth is associated with increases of the heart size, stroke and minute volume. At the same time, the bodily physical performance/ functionality may be modified by rea-sonably rated (by scopes and intensities) physical workloads. The study was designed to analyze the age- and fitness-specific anthropometrics variations in the speed skaters` adaptation periods. The national study reports show the age-specific adaptation being dependent on the physical training workloads, models and intensities. Objective of the study was to rate the age-specific anthropometrics variations in the speed skating sport. We made detailed analyses of the muscle and fat mass variations versus the anthropometric data in the training process to obtain the anthropometrics (including limb length rates) variation profiles. Sampled for the tests were 58 skaters classified into 5 groups by the fat to muscle mass ratios to find the group anthropometrics variations.